Effectiveness of Serious Game Activities in Raising Palliative Care Awareness Among Nursing Students. - Bahar, Vardar Inkaya; Cakmak, Betul; Bilgehan, Tugba; Alwawi, Abdallah; Calik, Afra (CIN: Computers, Informatics, Nursing, 2026)
Serious games have an important role in nursing education to support the development of students' knowledge, skills, satisfaction, and self-confidence. Serious games in the development of basic nursing skills are defined as interactive computer applications that present a challenging goal, offer an enjoyable and engaging experience, incorporate scoring mechanisms, and equip users with useful skills, knowledge, or attitudes. They provide students with opportunities for active learning, solving clinical problems, and gaining experience in a risk-free environment. Serious gaming applications ensure that education is not interrupted, especially in situations such as disasters and epidemics. Gamification-based education has recently become one of the e-learning methods used in nursing education. This study was conducted to evaluate the effectiveness of serious game activities in raising palliative care awareness among nursing students at Al-Quds University in Palestine, where gamification had not been previously utilized. This study employed a single-group quasi-experimental pre-test post-test design to evaluate the effectiveness of a serious game in raising palliative care awareness among nursing students. The findings reveal a statistically significant increase in students' palliative care knowledge scores following the e-learning and serious game activity (t = −3.659; P <.001). Post intervention, the difference between pre-test and post-test scores was found to be statistically significant for both female (P =.022) and male (P =.023) students, fourth-year students (P =.003), students with palliative care experience (P =.004), those who had taken 5 or more nursing courses with clinical practice (P =.009), and students who had previously received palliative care education (P <.001). In conclusion, since serious game-based educational games can positively impact nursing students' knowledge, skills, and self-confidence, they should be added to the curriculum by combining them with traditional education.